Trends on Axillary Surgery in Nondistant Metastatic Breast Cancer Patients Treated Between 2011 and 2015: A Dutch Population-based Study in the ACOSOG-Z0011 and AMAROS Era. Issue 6 (December 2018) - Poodt, Ingrid G. M.; Spronk, Pauline E. R.; Vugts, Guusje; van Dalen, Thijs; Peeters, M. T. F. D. Vrancken; Rots, Marjolijn L.; Kuijer, Anne; Nieuwenhuijzen, Grard A. P.; Schipper, Robert-Jan
Abstract : Objectives: To evaluate patterns of care in axillary surgery for Dutch clinical T1-4N0M0 (cT1-4N0M0) breast cancer patients and to assess the effect of the American College for Surgeons Oncology Group (ACOSOG)-Z0011 and After Mapping of the Axilla: Radiotherapy Or Surgery (AMAROS) trial on axillary surgery patterns in Dutch cT1-2N0M0 sentinel node positive breast cancer patients. Background: Since publication of the ACOSOG-Z0011 and AMAROS trial, omitting a completion axillary lymph node dissection (cALND) in sentinel node positive breast cancer patients is proposed in selected patients. Methods: Data were obtained from the nationwide Nationaal Borstkanker Overleg Nederland breast cancer audit. Descriptive analyses were used to demonstrate trends in axillary surgery. Multivariable logistic regression analyses were used to identify factors associated with the omission of cALND in cT1-2N0M0 sentinel node-positive breast cancer patients. Results: Between 2011 and 2015 in cT1-4N0M0 breast cancer patients, the use of sentinel lymph node biopsy as definitive axillary staging increased from 72% to 93%, and (c)ALND as definitive axillary staging decreased from 24% to 6% ( P < 0.001). The use of cALND decreased from 75% to 17% in cT1-2N0 sentinel node-positive patients ( P < 0.001). Earlier year of diagnosis, lower age, primary mastectomy, invasive lobular subtype, increasing tumor grade, and treatment in a nonteaching hospital were associated with a lower probability of omitting cALND ( P < 0.001). Conclusions: This study shows a trend towards less extensive axillary surgery in Dutch cT1-T4N0M0 breast cancer patients; illustrated by an overall increase of sentinel lymph node biopsy and decrease in cALND. Despite this trend, particularly noticed in cT1-2N0 sentinel node-positive patients after publication of the ACOSOG-Z0011 and AMAROS trial, variations in patterns of care in axillary surgery are still present. Abstract : Supplemental Digital Content is available in the text